Comparison of measuring the noise level of glass wool soundproofing material using a sound level meter and the KY-037 noise measuring instrument - Indah Pratiwi Tanjung; Masthura Masthura; Nazaruddin Nasution (Universitas Riau, 2024)
The problem that people often face, both at home and in public places, is noise that disturbs concentration and comfort. Noise can be measured by sound level measurement, namely by measuring the intensity or loudness of sound in hertz and sound waves in decibels (dB). Then noise can be reduced by materials that can absorb sound, one of which is glass wool. The purpose of this research is to make a noise-measuring instrument, find out the effectiveness of damping materials, and compare the results of measuring noise levels. The measuring instrument for noise in this study is the sound level meter (SLM) using a KY-037 sound sensor programmed with Arduino Uno as a microcontroller. The results of noise measurements using a factory standard SLM and noise measurement tool KY-037 obtained an average factory standard SLM measurement of 72.23 dB and the average measurement of the KY-037 noise meter is 67.67 dB. From the measurement results with the two tools, the difference in comparison is 4.56 dB with a percent deviation of 6,33%. Then the results of testing the glasswool sound-dampening material with a comparison of the two measuring devices obtained that each sound intensity absorption was 17.9 – 28.5 dB and the effectiveness of the reduction was 21.8% – 34.9%.